A Systematic Review of Educational Damages in Children of Divorce - Hosseinzadeh Dashti, Marziyeh; Salehi, Keyvan; Keshavarz Afshar, Hossein; Javadipour, Mohammad (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The primary objective of this study was to examine the educational damages faced by children of divorce. Divorce is a significant life event that imposes stress on the entire family, especially on children.Methods: This study employed a systematic review of existing literature to identify key educational damages faced by children of divorce. A total of 3,296 articles were initially retrieved from databases, and through a rigorous selection process based on relevance, 27 studies were chosen for in-depth analysis. The indicators were categorized into 9 criteria using a coding framework, with each indicator representing a unique educational challenge or damage.Findings: The review identified 72 educational indicators categorized into key themes such as academic decline, dropout rates, concentration and attention issues, cognitive development impairments, and reduced resources for education. The most frequent issues were poor academic performance, lack of concentration, and dropout rates. Children from divorced families exhibited significantly more challenges in school performance, motivation for achievement, and learning compared to those from intact families. The absence of a stable emotional and financial environment exacerbated these issues, further contributing to academic setbacks.Conclusion: The findings highlight the severe impact of parental divorce on children's educational performance and mental well-being. Academic decline, lack of concentration, and emotional maladjustment are common issues, often leading to school dropout. Effective interventions, including parental education and structured support programs, are crucial to reducing the educational damages faced by children of divorce. Schools and counselors must be trained to address these challenges and work collaboratively with parents to create a supportive learning environment.